Advancements in robotic pancreaticoduodenectomy: Innovations and future directions - Hao Hu; Keke Lv; Tianlin He (Intelligent Surgery)
In recent years, robot-assisted surgery has advanced significantly and has emerged as a vital approach for the treatment of benign and malignant pancreatic diseases. Robotic pancreaticoduodenectomy, one of the most critical pancreatic surgical modalities, is distinguished by its high surgical difficulty and risk. The focus of recent scholarly discussions has been on ensuring the safety and feasibility of the procedure. Drawing from the expertise of our unit's primary diagnostic team, this article provides an overview of the progress in robotic pancreaticoduodenectomy, encompassing patient selections, surgical approaches, identification of significant anatomical structures, and pancreaticojejunostomy techniques.